Comparison between using hepatocellular carcinoma (HCC) risk scores and the HCC national guideline to identify high-risk chronic hepatitis B patients for HCC surveillance in Thailand - Rattananukrom C. (2023)
Background and Aim: Hepatocellular carcinoma (HCC) surveillance in hepatitis B virus (HBV) patients is currently based on age/sex/cirrhosis, uses ultrasound abdomen every 6–12 months, and is a resource burden. HCC risk scores have been developed to classify HCC risk for surveillance. The number of HBV patients needing surveillance when HCC risk scores are used may be different from the current recommendation with implications on the resources needed for HCC surveillance. Methods: HBV patients from the liver clinic were included and classified as non-cirrhotic/cirrhotic and untreated/treated for analysis. Each subgroup was analyzed using REACH-B, CU-HCC, LSM-HCC, GAG-HCC, and mPAGE-B risk scores as appropriate. The change in the number of patients needing HCC surveillance using the above risk scores was calculated. Results: Seven-hundred and thirteen HBV patients were included, of whom 361 (50.6%) were male with mean age 55.43 years, and 76 (10.7%) had cirrhosis. In the untreated, non-cirrhotic subgroup, the percentage change of patients needing HCC surveillance was −69.5, −58.9, −58.8, and −54.1% when GAG-HCC, LSM-HCC, CU-HCC, and REACH-B were used compared to traditional criteria, respectively. In the treated, non-cirrhotic subgroup, the percentage change of patients needing HCC surveillance decreased by −80, −75.2, −75.2, and −2.8% when GAG-HCC, CU-HCC, REACH-B, and mPAGE-B were used, respectively. For the cirrhotic group, HCC risk scores did not make much difference. Conclusion: The use of HCC risk scores in non-cirrhotic HBV patients reduced the number of patients needing surveillance greatly. HBV cirrhotic patients should have HCC surveillance without the need for risk score calculation. Patients with a family history of HCC should undergo surveillance until proven unnecessary in prospective trials.